Chiasm in Zephaniah 3:14-17 – A new proposal - S.D. Snyman (Acta Theologica)
This contribution focuses on Zephaniah 3:14-17 and investigates the chiastic structure of the pericope methodologically. The history of research on this unit shows that not all commentaries recognise the chiastic structuring of this unit, while others opt for a parallelism rather than a chiastic structure. The reason why the chiastic structuring will be the focus of this investigation is that, while scholars, in more recent research, have recognised the chiastic structuring of verses 14-17, there is a difference of opinion on how to view the chiastic structuring. As a solution to the problem, a new proposal as to how to view the chiastic structure is suggested. According to the results of this research, an interesting and complex chiastic structure has been detected and can be schematised as follows: A-BC-D-D-C-B-A. Finally, the article briefly mentions some implications of the new proposal.